A Study of the Correlation of Obesity with Sex Hormones in Young Male Adults (International Journal of Physiology, 2020)
Background: Epidemiological studies support a bidirectional relationship between serum testosteroneand obesity as well as between testosterone and the metabolic syndrome. Low serum total testosteronepredicts the development of central obesity and accumulation of intra-abdominal fat. Also low total andfree testosterone and sex hormone binding globulin (SHBG) levels are associated with an increased risk ofdeveloping the metabolic syndrome, independent of age and obesity.Method: A cross sectional study was conducted on 100 male medical students (age 18 to 24 yrs). Bloodsamples were collected and investigated for serum testosterone level. Anthropometric measurements-BMI,Waist circumference and waist to hip ratio (WHR) were done.Results: 57 subjects out of 100 subjects with BMI 25 and serum testosterone level near to lower end of normal range.26 subjects with WHR 90 and serum testosterone level near to lower end of normal range.Conclusion: Serumtestosterone level increase with decrease in BMI and WHR. serumtestosterone leveldecrease with increase in BMI and WHR.Hence Sex hormone (Androgen) level is inversely related withobesity